Sustainable Washing for Denim Garments by Enzymatic Treatment - Khan, Md Mashiur Rahman; Mondal, Md Ibrahim H; Uddin, Md Zulhash (Journal of Chemical Engineering, 2013)
Denim garment is the most preferred of todays youth. This paper presents the effect of enzyme wash using cellulase enzyme on the properties of denim garments to develop novel design and fashion. Three parameters in enzyme washing namely concentration of enzyme, washing temperature and time at pH 5.5 were considered. To investigate the optimum washing condition, indigo dyed cotton denim garments (trousers) were chosen and processed by enzyme with the concentration of 0.5% to 3.5%, temperature 40°C to 70°C and time 20 min to 60 min for the achievement with desired worn and aged effect. The effect of each parameter is discussed, and denim garments properties like tensile strength, elongation at break, weight loss, stiffness, water absorption, shrinkage, color fading and morphological values by SEM were evaluated. The optimized washing condition for the best value is 2% enzyme concentration at 55°C for 40 min. DOI: http://dx.doi.org/10.3329/jce.v27i1.15854 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 1, June 2012: 27-31